Management of Equality Program Development in Non-Formal Education Unit (SPNF) SKB of Kubu Raya District - Edy Purwanto; Aunnurahman Aunnurahman; Wahyudi Wahyudi (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to (1) find out the stages of planning the development of an equality program in SPNF SKB of Kubu Raya District; (2) knowing the implementation of the Equality program development in the SPNF SKB of Kubu Raya District; (3) knowing the coordination of the implementation of the Equality program development in SPNF SKB of Kubu Raya District; (4) knowing the evaluation of the Equality program development in the SPNF SKB District of Kubu Raya District. This type of research is a case study research with a descriptive research approach. The results of this study are (1) program planning of the UPT SPNF of the Kubu Raya District SKB involving participation from within the institution, namely the UPT SPNF SKB of Kubu Raya District and outside the institution, namely the Kubu Raya Education and Culture Office as policy makers; (2) UPT SPNF SKB of Kubu Raya District has implemented anequality program in SPNF SKB Kubu Raya District ; (3) UPT SPNF SKB of Kubu Raya District has carried out a fairly good coordination with the work units involved in program development, both with government institutions andinstitutions outside the government, in addition to good communication between each work unit in SPNF SKB of Kubu Raya District; (4) UPT SPNF SKB of Kubu Raya District has conducted an evaluation to find out the development ofthe Equality program in SPNF SKB of Kubu Raya District